PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Perioda Tahun 2009-2011) - Dewi Mayasari, 09.05.52.093; Indarti, MG. Kentris (Students Journal of Accounting and Banking, 2013)
This study aimed to examine the effect of Intellectual Capital (IC) with key components such as capital employed or physical capital, human capital, structural capital, the companys financial performance as measured by Return on Assets (ROA), Return on Equity (ROE), and earnings per Share (EPS). The data used in this study is 74 x 3 = 222 manufacturing company data gained from the Indonesia Stock Exchange in 2009-2011 were downloaded from the site www.idx.co.id. This study uses a model pulic, capital employed or physical capital, human capital, structural capital and multiple regression analysis were used to examine the relationship between VAICTM the companys financial performance. The results of this study indicate that the variable of human capital and structural capital affecting the companys financial performance, while only variable capital employed does not affect the companys financial performance. Overall VAICTM have a significant relationship to the financial performance of the company. Keywords: Intellectual Capital (Capital employed or physical capital, human capital, structural capital) Corporate Financial Performance (ROA, ROE, EPS).